Physiological Changes in Jeju Crossbred Riding Horses by Swim Training - Kang, Ok-Deuk (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2012)
The changes in physiologic parameters by swim exercise duration were examined in five female well-trained Jeju crossbred riding horses that had riding experience of more than three years without swim training experience. The horses were performed with swim exercise for 10 min (60.0 m/min) once a day for 14 days. Physiologic characteristics and haematic parameters were measured before swimming, immediately after swimming, and after a 10 min rest at first day (D(0)), 7 days (D(7)), and 14 days (D(14)) of training. After 14 days of swim training, heart rate (p<0.05), blood glucose (p<0.05), lactate concentration (p<0.001), packed cell volume (p<0.01), and hemoglobin (p<0.01) measured immediately after swim and after 10 min rest showed significant lower values than those of D(0). The results illustrate the benefits of swim training for riding horses and the need for the establishment of swimming routines of appropriate duration and intensity to maximize the advantages of swim training.